PENINGKATAN PENGETAHUAN MENGENAI STIMULUS PADA ANAK USIA âGOLDEN AGEâ DI KELAS PARENTING TAMAN PAUD UNIVERSITAS ESA UNGGUL - Vionalita, Gisely (Universitas Esa Unggul, 2016)
AbstractThere was increasing in school dropout ratesÂ (3,14%) due to the unpreparedness of the childs brain development to face the formal education might beÂ caused by low stimulus developmental duringÂ golden age period. The development of science has led us of the important role of stimuli from parents on the development of children aged 0-5 years. The objective of this parenting class is to increase the parents awareness about the importance of the stimuli that can be done from family. The stimuli can be done in various ways according to the age of the child. Stimulation of this child will have an impact on their quality of life in the future. The provision of extension materials on how to stimulate the development and optimization childs brain is given in class parenting Taman PAUD UEU divided into the first session, a paradigm shift regarding the major education obtained at school, but should start from the family, the second session of exposure of the material containing about how stimulus for children develop the ability of brain function that can be done by parents, the third session of motivation to increase the desire and willingness of parents in stimulus to brain development in children and continued with last session, the question and answer session can be interspersed with the consultation issue. Implementation considered highly successful in increasing parental knowledge in stimulating children. In summary, it can be concluded that the activities of education about how to stimulate the childs brain development and optimization is given in parenting classes in Taman PAUD UEU have demonstrated the increasing of knowledge and understanding of the importance of how to maximize the ability of a childs brain function to create a quality of human resources in the future.Â Keywords: PAUD, early children, parenting classÂ AbstrakTingginya angka putus sekolah yang mencapai 3,14% dapat disebabkan oleh ketidaksiapan perkembangan otak anak dalam menghadapi pendidikan formal. Hal ini dapat disebabkan oleh rendahnya stimulus perkembangan diusia golden age. Perkembangan ilmu pengetahuan telah mengantarkan kita akan pentingnya peranan stimulus/rangsangan dari orang tua terhadap perkembangan anak usia 0-5 tahun. Pelaksanaan kelas parenting ini bertujuan untuk meningkatkan kesadaran orang tua akan pentingnya stimulus yang dilakukan di lingkungan rumah. Pemberian stimulus tersebut dapat dilakukan dengan berbagai cara sesuai dengan usia anak. Penstimulusan anak ini akan berdampak terhadap peningkatan kualitas hidup anak dimasa yang akan datang.Â Pemberian materi penyuluhan mengenai cara menstimulus perkembangan dan mengoptimalan otak anak diberikan di kelas parenting di Taman PAUD UEU dengan dibagi menjadi sesi pertama, perubahan paradigma mengenai pendidikan utama didapatkan disekolah, namun seharusnya dimulai dari keluarga, kedua, sesi pemaparan materi yang berisikan mengenai cara stimulus untuk mengembangkan kemampuan fungsi otak anak yang dapat dilakukan oleh orang tua, ketiga, sesi pemberian motivasi untuk meningkatkan keinginan dan kemauan orang tua dalam melakukan stimulus untuk perkembangan otak anak dan dilanjutkan dengan sesi terakhir, yakni sesi tanya jawab yang dapat diselingi dengan konsultasi masalah. Pelaksanaan dinilai sangat berhasil dalam meningkatkan pengetahuan orangtua dalam menstimulus anak. Secara kumulatif, dapat disimpulkan bahwa kegiatan penyuluhan mengenai cara menstimulus perkembangan dan mengoptimalan otak anak yang diberikan di kelas parenting di Taman PAUD UEU telah menunjukkan peningkatan pengetahuan dan pemahaman mengenai pentingnya cara memaksimalkan kemampuan fungsi otak anak untuk menciptakan generasi yang berkualitas.Â Kata kunci: PAUD, anak usia dini, kelas parenting